A study of the information-seeking behavior of history researchers at the University of the Philippines Diliman - Artuz, Christopher C.; Sison, Josephine C. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
This study focused on the information-seeking behavior of history researchers at the University of the Philippines in Diliman. The respondents consisted of eleven (11) history researchers who are currently conducting research studies. The manner of fulfilling one's information need is greatly affected by an understanding of the system (i.e., a library or information center as an information system) and the actions one takes in seeking information. How do these researchers conduct their research? What are the common problems of researchers in seeking information? What are the factors to be considered for effective research?
Using Kuhlthau's model of information-seeking which this study applied on selected history professors currently conducting research, this study determined the information-seeking behavior of UP history researchers. In-depth interviews were conducted to know the behavior of these history professors from the stage of initiating their research tasks, during the stage when they were actually gathering data for their research studies, until the search closure.
It was found that the common factor that influenced all the researchers is the personal interest in a certain topic. The services rendered by the Filipiniana Section of the U.P. Main Library are considered sufficient by the researchers. It was also found that the information needs directly dictates the necessary tasks or activities the researchers must accomplish. This aspect depends on the type of the topic a researcher has.
The study found that the behavior of UP history researchers are primarily based on their interest, their field of study, their information needs, the available information on their research topic of interest and their involvement in their research. The following conclusions are drawn: history researchers initiate tasksbecause they have interest in the topic and this motivates them. In selecting a topic, the following factors are taken into consideration by history researchers: personal interest, feasibility of the research (information available, time available, and scope and limitation/time-frame of the research) and its contribution to the body of knowledge. During the stage of pre-focus exploration, history researchersemphasize the importance of the following actions: taking down note on facts and ideas/survey notes, bibliographic description/data making, and reading lots of references. During the focus formulation stage, most of them have flexible frameworks for the possibility of changing their focus. This matter generally depends on the availability of information on their topic of research. In gathering of data, there are three common steps the history researchers do, namely: exhausting possible resources, locating the materials, and producing a copy or borrowing the materials for extensive reading and analysis. They evaluate the materials by scanning its contents, and checking the table of contents and index. They would only consider their research as finished material or completed if they are already satisfied with the information it contains; their questions are answered with enough details; and the research has already a conclusion that they can be able to defend based on their findings. Most of them are willing to extend their research in some grace period when the cited reasons above are not met.
An understanding of how tasks are undertaken by users in seeking information provides us with better insights on how to meet their information needs. Furthermore, they provide important inputs in enabling us to design more user-centered information system and services. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library use studies -- Philippines -- Quezon City; Historians -- Philippines -- Quezon City